Inovasi Pendidikan di SMK Tamansiswa 1 Imogiri Yogyakarta di Era Disrupsi - Arditya Furqon Wicaksono (SALIHA: Jurnal Pendidikan & Agama Islam, 2019)
This article discusses Educational Innovation at the Imogiri 1 Tamansiswa Vocational School in Yogyakarta in the Disrupted Era. Innovation or renewal in the world of education in this era of disruption is needed so that more conceptual and conducive learning can be created. Educational innovation here implies a reformative and qualitative change that is different from the previous one and intentionally held to improve capabilities in order to achieve the objectives of National Education. Disruption replacing old physical technology with digital technology that produces something truly new and more efficient, is also more useful. Imogiri Yogyakarta Tamansiswa 1 Vocational School has implemented Education Innovation in the Disruption era by learning through English-language songs, coopertive learning, mural fashion shows of Kartini kebaya clothes, the use of web sites, online PPDB and the megajar group work method. Digital technology can help teachers learn faster and more effectively to change and develop.